Influence of Covid 19 on morphological and cardiovascular status of professional handball players - Gadžic, A.; Živkovic, A.; Stojmenovic, T. (SportLogia, 2021)
Handball is one of the very popular sports games in the world. The current COVID 19 pandemic directly affects handball players in the training and competition processes from all age categories but professional players seem to be at a higher risk of contracting the disease. This study aimed to assess morphological and cardiovascular status of 20 participants, professional handball players who compete at elite competition rank, and therewith to adjust their training process and to test the differences between COVID 19 positive and COVID 19 negative participants. Testing included measurements of basic morphological parameters while the function of the cardiovascular system (CVS) was assessed at rest and effort - exercise stress test with Vita Maxima protocol. The results of t-test did not show a statistically significant difference in morphological and cardiovascular characteristics of participants who had COVID 19 infection (with a positive PCR test), who had symptoms of infection but no PCR test for the virus, and those who did not contract COVID 19.